74.9k views
4 votes
Which is the simplified form of (9c^-9)^-3
b 1/729 c^27

2 Answers

3 votes

Answer:

Step-by-step explanation: the answer is b

User Bitwit
by
5.9k points
4 votes

ANSWER


(9 {c}^( - 9) )^( - 3)=\frac{{c}^( 27) }{729}

Step-by-step explanation

The given expression is


(9 {c}^( - 9) )^( - 3)

Recall that:


({a}^(m) )^(n) = {a}^(mn)

We use the law of exponents to get


(9 {c}^( - 9) )^( - 3) = 9^( - 3) {c}^( - 9 * - 3)

Let us multiply in the exponents to get:


(9 {c}^( - 9) )^( - 3) = 9^( - 3) {c}^( 27)

Recall again that:


{a}^( - m) = \frac{1}{ {a}^(m) }

This implies that:


(9 {c}^( - 9) )^( - 3) = \frac{1}{ {9}^( 3) } * {c}^( 27)

We expand the power to get:


(9 {c}^( - 9) )^( - 3) = (1)/(9 * 9 * 9) * {c}^( 27)


(9 {c}^( - 9) )^( - 3)=(1)/(729) * {c}^( 27)

We multiply out to get:


(9 {c}^( - 9) )^( - 3)=\frac{{c}^( 27) }{729}

User Andrew Schwartz
by
6.7k points